Ultrathin polyethyleneimine (PEI) films for culturing of the human mesenchymal stromal cells (hMSCs) - Liudmila M Mezhevikina; Dmitriy A Reshetnikov; Maria G Fomkina; Evgeniy E Fesenko (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
A polymer polyethyleneimine (PEI) can be used in various cell technologies, including the nonviral transfection of animal and human eukaryotic cells. We used the polymer (in the 1 mg/ml concentration) to produce the ultrathin films at the culture plastic that could enhance the adhesive properties of the human mesenchymal stromal cells (hMSCs) isolated from the heterogeneous cell population of the marrow. Our study demonstrated that the PEI films prevent cell-to-cell cooperation and "glomeration" of hMSCs at the surface of a cultural plate, and enhance hMSCs viability and metabolic activity in vitro. The stimulating effects of PEI on cell proliferation are negligible. Moreover, the immobilization of the human platelet lysate (PL) in 5% or 10% concentrations into the PEI solution increases hMSCs viability and effectiveness of their culturing under the deprivation condition and in the serum-free medium. We suggest to use the PEI films containing the immobilized growth factors in the regenerative medicine - at the stages of hMSCs isolation and growth of their biomass.